Correlation between Serum Ascites Albumin Gradient and Endoscopic Grading of Esophageal Varices in patients with cirrhosis - Talha Khalid, Rabia Islam Abbasi, Sidrah Muhammad Rafiq, Hira Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The serum-ascites albumin gradient (SAAG) is a medical calculation that can help determine the cause of your ascites. The SAAG may be a more effective discriminator than the usual method of dividing ascites fluid into transudates and exudates. Objective: The objective of this study was to see if there was a link between the serum ascites albumin gradient and the endoscopic grading of esophageal varices in cirrhotic individuals. Materials and Methods: This Cross-sectional study was conducted in Unit II, Department of Medicine, Lahore General Hospital, Lahore during 3-10-2018 to 3-4-2019. A total of 60 patients who met the study’s inclusion criteria were included. Blood sample was taken and sent to the laboratory of the hospital for assessment of serum albumin level and SAAG was calculated. Results: Results of this study showed positive moderate correlation between grades of varices and SAAG i.e. r= 0.661, p-value=0.000. Esophageal varices appear to be directly linked to the severity of SAAG. Conclusion: In individuals with cirrhosis, there is a moderately strong significant association between the SAAG and the endoscopic grading of esophageal varices. In cirrhotic individuals, SAAG may be a useful biomarker for EV development.